PENGARUH SKEPTISISME PROFESIONAL, SITUASI AUDIT, ETIKA AUDIT, PENGALAMAN DAN KEAHLIAN AUDIT TERHADAP KETEPATAN PEMBERIAN OPINI AUDITOR - Surna Lastri; Fitri Yunina; Anggun Dwi Handayani (University Muhammadiyah Aceh, 2021)
This study aims to examine the effect of professional skepticism, audit situations, audit ethics, audit experience and expertise on the accuracy of giving auditor opinion by accountants to the BPKRI Perwakilan Aceh. This study uses quantitative methods. The sample in this study was all auditors at the BPK RI Perwakilan Aceh. Data collection techniques using questionnaires were obtained by distributing questionnaires to auditors working at the BPK RIPerwakilan Aceh. The analytical method used is multiple linear regression. The results of this study found that professional skepticism, audit situations, audit ethics, audit experience and expertise have an effect on the accuracy of giving auditor opinion by accountants, both simultaneous and partially.